Pengaruh Beberapa Faktor Terhadap Produk Pada PT. Indo Brush Utama Di Makassar - Bintang Balele; Mardiana Ibrahim (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The aim of the research is to determine the influence of service policy, demand and price on product improvement at PT. Indo Brush Utama in Makassar, South Sulawesi Province. And to find out the most dominant factors that influence product improvement at PT. Indo Brush Utama in Makassar, South Sulawesi Province. The research method used is a quantitative research method. Simultaneously shows that service policy factors (X1), demand (X2), and price (X3) have a significant effect on product sales in marketing at PT. Indo Brush Utama in Makassar. Partially, the price policy factor (X3) has a dominant influence on product sales, followed by service and demand factors in the sales of this company's products. This shows that the more varied the price policy factor increases product sales at PT. Indo Brush Utama in Makassar.